Analisis kedudukan nafkah dalam perkawinan perspektif hukum keluarga islam di Indonesia - Aazzu, Aazzu (Maliki Interdisciplinary Journal, 2025)
Maintenance (nafkah) is a central component in sustaining family resilience and represents one of the husband’s primary obligations within marriage. This study seeks to examine the legal position of maintenance in the framework of Islamic Family Law in Indonesia, drawing upon the Qur’an, hadith, Law No. 1 of 1974, and the Compilation of Islamic Law (KHI). Employing a library research approach, the study reviews statutory regulations, classical and contemporary fiqh literature, as well as prior scholarly works related to the duty of maintenance. The findings reveal that maintenance holds firm legal authority as a binding obligation for husbands throughout the marital relationship, except under specific circumstances such as when the wife is deemed nusyuz. Furthermore, the research highlights that disputes over maintenance are among the most frequent cases addressed in Religious Courts. A comprehensive understanding of maintenance is therefore essential to enhance legal awareness and promote harmony within the family.